An Analysis of the Verbal Marker tsa in Luguru - Petzell, Malin (Studia Orientalia Electronica, 2020)
This paper deals with a morphosyntactic phenomenon found in the under-described Bantu language Luguru, spoken in central Tanzania: the verbal marker tsa. This marker encodes shared knowledge or shared reference. The meanings conveyed by the marker stretch from ‘at a specific time’ or ‘at that place’ to ‘as we know’, or even ‘for that reason’. In Mkude’s grammatical description of Luguru from 1974, there is a mention of a marker (zaa) signalling what he calls “recollected reference”, which restricts the event to one specific moment in the past; this marker is believed to have developed into today’s tsa.